KEBIJAKAN HUKUM PIDANA TERHADAP PROSTITUSI ONLINE DI KALANGAN REMAJA PERSFEKTIF KEADILAN - Widhy Andrian Pratama; Sitti Khadijah Nurfajri; Gunawang Gunawang (Jurnal Jendela Hukum, 2026)
Online prostitution practices involve not only posting content on social media but also utilizing complex communication strategies to implicitly attract consumers. The inclusion of photos or videos of sex workers and the use of keywords such as "Open BO" serve as code words for potential clients, allowing sexual transactions to be arranged without explicitly mentioning the services. This research was conducted through a literature review, which included identifying legal issues, searching for relevant literature, and systematic legal analysis. The legal sources used were derived from relevant documents and literature, then analyzed in depth to obtain an objective, logical, and structured understanding of the law. The approach used was qualitative, with a literature review method supplemented by focus group discussions to enrich the analytical perspective. The author concludes that adolescents' lack of understanding of sex leads to limited knowledge about sexuality. To prevent adolescents from engaging in prostitution, sex and reproductive health education at the secondary school level is crucial. Prostitution not only creates social problems but also carries a high risk because perpetrators are suspected of being a source of AIDS transmission due to casual sex without protection such as condoms.